The woman metaphor of Ezekiel 16 and 23 : a victim of violence, or a symbol of subversion? - Stiebert, Johanna (Old Testament essays, 2002)
Textually-speaking, Ezekiel 16 and 23, being disjointed and full of internal repetitions, are difficult. In terms of content, too, both chapters are notable for their detailed and particularly graphic, vulgar and brutal use of the prophetic woman metaphor. These features have been accounted for variously. The paper reviews psychoanalytical and feminist explanations, before proposing three alternative critical approaches, which all incorporate the idea of the texts stemming from a context of turbulent social conditions. These three approaches examine the metaphors from the perspective of the grotesque, with regard to antilanguages and in the light of a phenomenon known in sociology as 'deviance amplification'.